Investigation, characterization and prevalence assessment of various fungalcontaminants in sugarcane in vitro cultures - Hariprasath M; Bhukya Srinivas; Shivangi Kansara; Priya John (Journal of Sugarcane Research)
Microbial contamination poses a signiﬁcant challenge during the tissue culture process. The current investigation focuses on examining fungal contaminants in in vitro cultures of two distinct sugarcane varieties, CoN 13073 and CoN 707, aiming at their detection,  isolation,  and  identiﬁcation.  The  study  employed  the  fungal  tip  isolation  method  to  isolate  and identify  fungal contaminants. Six diﬀerent fungal species were identiﬁed, including Aspergillus ﬂavus Link, Penicillium sp., Macrophomina phaseolina (Tassi) Goid., Curvularia sp., Rhizopus sp., and an aseptate sterile fungus, based on their cultural and morphological characteristics from contaminated cultures of the two sugarcane varieties. The frequency of fungal contaminants associated with in vitro cultures of sugarcane was assessed in both varieties at 15-day intervals from explant inoculation to 60 days. Among the six isolates, A. ﬂavus (21.62-33.33%) was the most prevalent across all time intervals in both varieties, followed by Penicillium sp. (14.81-31.58%), Curvularia sp. (0-26.32%), M. phaseolina (0-21.62%), and Rhizopus sp. (15-19.05%). The least frequent fungal contaminant observed was the aseptate sterile fungus (4.76-11.76%) at all time intervals in both varieties.